NATIONAL UNREST IN THE KISHLAKS OF FERGANA VALLEY (LATE 19TH CENTURY) (Scientific journal of the Fergana State University, 2023)
Based on archival documents and available literature from the colonial period of the Russian Empire, the article examines the national unrest in the villages of Fergana Valley. The author analyses the hard state of the dekhkans, their struggle against colonial domination and local feudals, as well as the consequences of the national unrest in the period concerned.